Screening porcine DNA in collagen cream cosmetic products - Zabidi A.R.; Fauzi F.N.; Abd Razak F.N.; Rosli D.; Jamil M.Z.M.; Wan Ibrahim W.K.; Yahaya N. (Rynnye Lyan Resources, 2024)
Indexed by Scopus/ERA